Pengaruh Rasio Kitosan-Sodium Tripolifosfat Terhadap Pengendalian Antraknosa (Colletotrichum gloeosporioides) Pada Mangga Kultivar Manalagi - Yadi Suryadi; Dwi N. Susilowati; I. M. Samudra (Jurnal Penelitian Sains, 2020)
Anthracnose disease caused by the fungus Colletotrichum gloeosporioides is one of the most important diseases on fruit trees. Chitosan material have been applied to many different application fields including disease biocontrol because of its  biocompatible and biodegradable effect. This research was aimed  to synthesize low molecular weight chitosan (LMWC) which prepared via enzymatic process using a bacterium Burkholderia cepacia E76 and ionic gelation method, using sodium tripolyphosphate (NaTPP), and to test their activity against C. gloeosporioides on mangoes fruits. In this study the effect of concentration and volume ratio of LMWC : NaTPP was determined based on particle characteristics, i.e particle size, polydispersity index, zeta potential and FTIR structure. The results showed that LMWC could be synthesized by means of enzymatic hydrolysis using chitinase originated from B. cepacia E76. The optimal nanoparticle conditions was obtained by concentration of 0.3% LMWC, 0.1% TPP with volume ratio 5 : 1, stirring for 30-60 min incubation with the particle size of  126.2 nm and ZP value of  25.5 + 6.1 mV. LMWC and nano chitosan product could be evidenced by FTIR analysis. Nano chitosan could inhibit the growth of C. gloeosporioides ranging from 61.28 – 96% under in vitro test.  The result of in vivo test on manggoes fruit cv Manalagi, showed that chitosan nano particle could effectively inhibit the growth of anthracnose (74.5%) at concentration of 0.3% LMWC, and 0.1% NaTPP with ratio 5:2 compared with control. Keywords: B. cepacia E76, chitinase, chitosan, low molecular weight, anti fungi